Social Assistive Robots: Assessing the Impact of a Training Assistant Robot in Cardiac Rehabilitation (2021)
According to the world health organization, cardiovascular diseases are a major cause of death worldwide. Cardiac rehabilitation programmes are dedicated to approach this problem and reduce mortality rates due to the presence of a second event. However, the adherence and motivation of patients to assist to these programmes is not the expected. Therefore, this paper presents the incorporation of a SAR system into a cardiac rehabilitation scenario, where a social robot had the role of a training assistant during the therapy, aiming to increase motivation and encourage people to continue with the therapy. This study carried out a longitudinal experimental setup with a total of 209 sessions observed for a group of 6 patients in a period between 3 and 6months. Results show that patients felt more encouraged to perform physical activity and continue with the rehabilitation when they perceived that monitored and supervised by the system, demonstrating that it can be implemented as a reliable tool that would potentially leverage tasks carried out by health professionals.